Increased Carotid Intima-Media Thickness in Female Patients With Fibromyalgia: A Preliminary Study - Hüma BÖLÜK; Gökhan Tuna ÖZTÜRK; Didem CÖMERT; Murat ERSÖZ (Archives of Rheumatology, 2015)
Objectives: This study aims to measure the carotid artery intima-media thickness (IMT) of patients with fibromyalgia (FM) by using ultrasound imaging and to investigate whether carotid IMT measurements were associated with the severity of FM. Patients and methods: Nineteen female patients (mean age 42.9±8.1 years; range 24 to 57 years) and 17 healthy female subjects (mean age 41.5±6.3 years; range 33 to 57 years) were included in this study. The Fibromyalgia Impact Questionnaire was used to determine the severity of FM. After clinical evaluation of the subjects, ultrasound imaging examinations of the carotid IMT were performed. Results: Right and left carotid IMT values were thicker in the patient group in comparison to the control group (p1=0.05, p2=0.03, respectively). Carotid IMT values were correlated with age and body mass index. Carotid IMT values did not have any correlation with blood glucose levels, creatinine levels, serum lipid profile and Fibromyalgia Impact Questionnaire scores in FM patients. Conclusion: Carotid IMT of FM patients seems to be affected. Our finding may have stemmed from endothelial dysfunction possibly due to increased sympathetic activity.